MOTIVASI DAN ETOS KERJA PENGANUT TAREKAT QADIRIYYAH-NAQSABANDIYYAH DI TIRTO PEKALONGAN - Muhammad Aba Yazid (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
Sufism is often considered a doctrine that does not support progress; accused of teaching people to distance themselves from the world and stagnating Islamic civilization. Many modern rationalists criticize Sufi teachings or tarekat for being inconsistent with advances in science and technology. This negative assumption made the tarekat (Sufi order) followers uncomfortable. Finding this skewed assumption, the researcher conducted a research on the relationship of Sufism in Qadiriyyah-Naqsabandiyyah (Sufi order of Qadiriyyah Naqsabandiyyah/TQN) with the work ethic of its followers in the Tirto Pekalongan area, Central Java. There are three objectives in this research, namely: First, to find out the motivation of the congregation to follow Qadiriyyah Naqsyabandiyyah in Tirto Pekalongan; Second, knowing the work ethic of the followers of the Qadiriyyah Naqsyabandiyyah in Tirto Pekalongan; Third, to explain the correlation between the Qadiriyyah- Naqsyabandiyyah and the work ethic of its tarekat followers. This research is a mixed study of qualitative, quantitative and descriptive which describes the relationship between TQN followers in Tirto Village, Pekalongan City and their work ethos. To explore data, researchers spread out a questionnaire and interview which were then analyzed and concluded. Some of the findings that the researchers found included: TQN practitioners in Tirto Pekalongan showed a high work ethic and TQN followers in Tirto Pekalongan had spiritual and social motivations.